2019
DOI: 10.1007/s40243-019-0151-2
|View full text |Cite
|
Sign up to set email alerts
|

CuIn0.7Ga0.3Se2 thin films’ properties grown by close-spaced vapor transport technique for second-generation solar cells

Abstract: In this paper, CuIn 0.7 Ga 0.3 Se 2 (CIGS) thin films are deposited on both glass (SLG) and glass/SnO 2 :F (SLG/FTO) substrates, by close-spaced vapor transport technique. The Hall effect measurements are performed in the temperature range (300-438 K) for the two SLG/CIGS samples namely CIGS1 and CIGS2, grown at substrate temperature (T s ) of 470 °C and 510 °C, respectively, to investigate the temperature effect on the electrical parameters such as hole concentration (p), conductivity (σ) and mobility (µ). As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…From Oulmi et al [64], noncrystalline PV cells were reported. These are in the second-generation and noncrystalline 5 International Journal of Photoenergy form of silicon which is new technology compared to monoand polycrystalline cells and would not be considered a mature technology as vast improvements in this technology are expected in the coming years.…”
mentioning
confidence: 99%
“…From Oulmi et al [64], noncrystalline PV cells were reported. These are in the second-generation and noncrystalline 5 International Journal of Photoenergy form of silicon which is new technology compared to monoand polycrystalline cells and would not be considered a mature technology as vast improvements in this technology are expected in the coming years.…”
mentioning
confidence: 99%